2020
DOI: 10.3390/polym12051048
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Design of New Efficient Energy-Performance Construction Materials with Rigid Polyurethane Foam Waste

Abstract: An ecological mortar is designed from industrial sub-products, with the objective of utilizing both the slag residues, generated during steel manufacturing processes, and the waste from Polyurethane Foam (PF) panels, generated during refrigerator chamber manufacturing processes. The ecological mortar design involves the dosing of Electric Arc Furnace (EAF) slag, together with finely ground Polyurethane Foam, cement, and additives. An energy efficient prefabricated block is designed with the mortar, for use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Since the material’s ability in storing energy depends not only by its mass and density but also by its specific heat, the HT-DSC allowed them to evaluate the material’s thermal inertia. Considering that the higher the thermal inertia, the greater the time for a polymer to reach thermal equilibrium with the surrounding media, they found good thermo-mechanical properties for the recycled materials [ 20 ].…”
Section: Thermal Techniques In Biopolymers’ Designmentioning
confidence: 99%
“…Since the material’s ability in storing energy depends not only by its mass and density but also by its specific heat, the HT-DSC allowed them to evaluate the material’s thermal inertia. Considering that the higher the thermal inertia, the greater the time for a polymer to reach thermal equilibrium with the surrounding media, they found good thermo-mechanical properties for the recycled materials [ 20 ].…”
Section: Thermal Techniques In Biopolymers’ Designmentioning
confidence: 99%
“…Although a coherent literature on the circular economy of cooling is sparse, there is emerging literature on managing cooling products at their end-of-life for some specific component parts. Briones-Llorente et al (151) studied how processed insulating foams from old and obsolete refrigerators can be recycled as insulating materials in the construction of buildings that require specific thermal comfort capacity, such as hospitals. However, the most attention has gone to the risks posed by cooling waste as sinks or banks for CFCs and HFCs, which respectively cause severe damage to the ozone layer and are potent short-lived GHGs.…”
Section: Production Of Circular Coolingmentioning
confidence: 99%
“…The authors concluded that adding the Sodium Carbonate is beneficial for the production of ultra-lightweight aggregates from sludge marine clay -Recycled or recovered content [143] To study the feasibility of producing mortar blocks incorporating Polyurethane Foam and electric arc furnace and test their thermal and mechanical behaviors Experimental study, software simulation, and case-study…”
Section: Experimental Studymentioning
confidence: 99%